(untitled) (Journal of actual problems of jurisprudence, 2016)
According to the UN Declaration on the Rights of Minorities, said about minorities as original national or ethnic, cultural, religious and linguistic groups, and obligation of states to protect their existence provides. The article discusses the legal regulation of the status of minorities Council of Europe, the importance of protecting persons belonging to national minorities, as an integral part of the international protection of human rights in the interests of equality, justice,stability, democratic security and peace in Europe.